Cancer cell stemness, responses to experimental genotoxic treatments, cytomegalovirus protein expression and DNA replication stress in pediatric medulloblastomas. Issue 7 (2nd April 2020) - Bartek, Jiri; Merchut-Maya, Joanna M.; Maya-Mendoza, Apolinar; Fornara, Olesja; Rahbar, Afsar; Bröchner, Christian Beltoft; Sehested, Astrid; Söderberg-Nauclér, Cecilia; Bartek, Jiri; Bartkova, Jirina
ABSTRACT: Despite recent progress in research on brain tumors, including identification of cancer stem-like cells (CSCs), little is known about the interplay of stemness with the commonly observed infection by the human cytomegalovirus (HCMV) and the widespread features of replication stress in these malignancies. To shed more light on these outstanding issues, here we combine immunohistochemical analysis of archival clinical specimens from a cohort of 25 human pediatric medulloblastomas, complemented by functional experiments and analytical approaches to examine three medulloblastoma cell lines. In the clinical samples, we find consistent, yet individually variable subsets of CSCs expressing the stem-cell markers CD133 and CD15, and a candidate marker VEGFR2, across the spectrum of endogenous DNA damage (γH2AX), expression of HCMV immediate early and late proteins, proliferation rate (Ki67) or molecular class of MB. Contrary to MB cell lines DAOY and D324, the D283 cells showed pronounced phenotypic features of stemness, associated with enhanced endogenous DNA damage, exceptionally high susceptibility to infection with HCMV, unorthodox signaling pathway response to ionizing radiation and hyperactive response to hydroxyurea-induced replication stress. Notably, single-molecule DNA fiber analysis revealed aberrantly slow replication fork progression, pronounced fork asymmetry and inability to timely recover from drug-induced fork stalling in stem-like D283 cells, all hallmarks of pronounced chronic replication stress and propensity to genomic instability. These findings provide insights into human medulloblastoma stemness phenotypes, with various susceptibilities to infection by HCMV and impact on replication fork (mal)function, with implications for better understanding pathogenesis and responses to treatment in pediatric brain malignancies. Abbreviations : CSC: cancer stem-like cells; FBS: fetal bovine serum; HCMV: human cytomegalovirus; MB: medulloblastoma; MBSC: medulloblastoma stem cells; MOI: multiplicity of infection; PBS: phosphate-buffered saline; RPA: replication protein A; RS: replication stress; SHH: sonic hedgehog; VEGFR2: vascular endothelia growth factor receptor 2.